2019
DOI: 10.1088/1475-7516/2019/10/065
|View full text |Cite
|
Sign up to set email alerts
|

General relativistic cosmological N-body simulations. Part I. Time integration

Abstract: This is the first in a series of papers devoted to fully general-relativistic N -body simulations applied to late-time cosmology. The purpose of this paper is to present the combination of a numerical relativity scheme, discretization method and time-integration algorithm that provides satisfyingly stable evolution. More precisely, we show that it is able to pass a robustness test and to follow scalar linear modes around an expanding homogeneous and isotropic space-time. Most importantly, it is able to evolve … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 145 publications
3
15
0
Order By: Relevance
“…Going beyond such linear corrections, recently the first Post-Newtonian cosmological simulations have been carried out (Adamek et al 2013(Adamek et al , 2016 which indicated however that back-reaction effects are small and likely irrelevant for the next generation of surveys. Most recently, full GR simulations are now becoming possible (Giblin et al 2016;East et al 2018;Macpherson et al 2019;Daverio et al 2019) and seem to confirm the smallness of relativistic effects. The main advantage of relativistic simulations is that relativistic species, such as neutrinos, can be included self-consistently.…”
Section: Post-newtonian Simulationsmentioning
confidence: 92%
“…Going beyond such linear corrections, recently the first Post-Newtonian cosmological simulations have been carried out (Adamek et al 2013(Adamek et al , 2016 which indicated however that back-reaction effects are small and likely irrelevant for the next generation of surveys. Most recently, full GR simulations are now becoming possible (Giblin et al 2016;East et al 2018;Macpherson et al 2019;Daverio et al 2019) and seem to confirm the smallness of relativistic effects. The main advantage of relativistic simulations is that relativistic species, such as neutrinos, can be included self-consistently.…”
Section: Post-newtonian Simulationsmentioning
confidence: 92%
“…The present general investigation is also useful to relax some restricting assumptions of Papers I and II, to better understand the relation to Newtonian averaged cosmologies [27], and to extend the range of applicability of the effective equations. It will in particular allow for their application to the analysis in terms of spatial averages of relativistic cosmological simulations which make use of non-fluid-orthogonal foliations (see the recent works [67,39]).…”
Section: Introductionmentioning
confidence: 99%
“…There are already numerical simulations that incorporate relativistic effects [44][45][46][47][48][49]. In order to facilitate the fit to and comparison with the most advanced research program: gevolution [48], we perform our calculations in Poisson gauge.…”
Section: Contentsmentioning
confidence: 99%